THE EFFECTIVENESS OF VIRAL MARKETING ON PURCHASE DECISIONS THROUGH CUSTOMER TRUST ON THE TOKOPEDIA PLATFORM - Hendrawan, Diky Angga; Nabilah, Anisah; Hamiduddin, Ahmad Yahya; Harto, Harto (Universitas Kuningan, 2024)
Viral Marketing is a type of marketing that is low-cost because it relies on social media to spread information. The phenomenon of online shopping is increasingly becoming the choice of many people, because shopping online can save time without having to go to a physical location to shop. There are several factors that consumers need to consider before making a purchasing decision, such as trust, where in making online transactions it is important to have certainty, ease in finding the desired product, and clear information about the product and how to buy. This study was conducted using descriptive and verification methods, which then produced conclusions and suggestions. Samples were collected using the Incidental Sampling method, with a total of 205 respondents. Based on the analysis that has been done, this study proves that Viral Marketing has a significant influence on Customer Trust. Furthermore, Customer Trust also has a significant influence on Purchasing Decisions. In addition, Viral Marketing has a significant influence on Purchasing Decisions.